BUDAYA TRI HITA KARANA SEBAGAI PEMODERASI PENGARUH KEPUTUSAN PENDANAAN PADA KINERJA KEUANGAN BPR KOTA DENPASAR - Yastini, Ni Putu Yeni Ari; Budiasih, I G.A.N; Dwija Putri, I G. A. Made Asri; Erawati, Ni Made Adi (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.11.NO.07.TAHUN.2022DO - 10.24843/EEB.2022.v11.i07.p03, 2022)
The purpose of the research conducted at Credit Banks in Denpasar City was to obtain evidence of the influence of Good Corporate Governance and resources on BPR's financial performance by using the application of Tri Hita Karana culture as a moderating variable.                 The data used is primary data collected through survey techniques using a questionnaire. as well as secondary data in the form of financial reports for rural banks in Denpasar which were obtained from the official website of the Financial Services Authority (OJK). The data analysis technique used is multiple linear regression analysis and moderated regression analysis (MRA). the determination of the sample is done by using the saturated sample technique. This study analyzes the primary data questionnaire from 58 respondents' answers, namely the directors and financial officers of BPRs located in Denpasar City and analyzes secondary data on BPR financial reports published on the official OJK website.                 The results obtained are that Good Corporate Governance has no effect on the financial performance of BPRs, does not affect the financial performance of BPRs, the Tri Hita Karana culture is not able to moderate the influence of Good corporate governance on the financial performance of BPRs, and the Tri Hita Karana culture is not able to moderate decisions on the financial performance of BPRs.